Comorbidity between mood and substance-related disorders: A systematic review and meta-analysis. (July 2022) - Saha, Sukanta; Lim, Carmen CW; Degenhardt, Louisa; Cannon, Danielle L; Bremner, Monique; Prentis, Finley; Lawrence, Zoe; Heffernan, Ed; Meurk, Carla; Reilly, John; McGrath, John J
Background and Objectives: Evidence indicates that mood disorders often co-occur with substance-related disorders. However, pooling comorbidity estimates can be challenging due to heterogeneity in diagnostic criteria and in the overall study design. The aim of this study was to systematically review and, where appropriate, meta-analyse estimates related to the pairwise comorbidity between mood disorders and substance-related disorders, after sorting these estimates by various study designs. Methods: We searched PubMed (MEDLINE), Embase, CINAHL and Web of Science for publications between 1980 and 2017 regardless of geographical location and language. We meta-analysed estimates from original articles in 4 broadly defined mood and 35 substance-related disorders. Results: After multiple eligibility steps, we included 120 studies for quantitative analysis. In general, regardless of variations in diagnosis type, temporal order or use of adjustments, there was substantial comorbidity between mood and substance-related disorders. We found a sixfold elevated risk between broadly defined mood disorder and drug dependence (odds ratio = 5.7) and fivefold risk between depression and cannabis dependence (odds ratio = 4.9) while the highest pooled estimate, based on period prevalence risk, was found between broadly defined dysthymic disorder and drug dependence (odds ratio = 11.3). Based on 56 separate meta-analyses, all pooled odds ratios were above 1, and 46 were significantly greater than 1 (i.e. the 95% confidence intervals did not include 1). Conclusion: This review found robust and consistent evidence of an increased risk of comorbidity between many combinations of mood and substance-related disorders. We also identified a number of under-researched mood and substance-related disorders, suitable for future scrutiny. This review reinforces the need for clinicians to remain vigilant in order to promptly identify and treat these common types of comorbidity.